Teologi Pernikahan Berbasis Matius 5:31-32 : upaya Penguatan Keluarga di GKPI Resort Saur Nauli Pargarutan - Ronald Patiar Hutabarat; Iwan Setiawan Tarigan (Pusat Riset dan Inovasi Nasional, 2025)
Marriage is a dynamic of life that is felt by everyone. Everyone certainly hopes to have a happy, safe, stable and lifelong marriage, but in reality there are many marriages that fail and end in divorce. Divorce is a form of broken household relationships or marriage relationships that are marked by separation. Strengthening the family through various activities facilitated by the church can be a solution to increase the congregation's knowledge of the true meaning of marriage. With a good understanding of the meaning of marriage itself, divorce cases can be avoided and will not be thought of as a solution to the conflict experienced in the household.